Harmonic acid-containing chilblain sphere and preparation method thereof

By loading hyaluronic acid and mixed colloids into Hantian crystal balls, and carrying out specific testing and processing, the problem of the weakening of gel performance caused by the direct addition of hyaluronic acid to the colloid system was solved, and the effects of improving taste and nutritional value were achieved. .

CN119326132APending Publication Date: 2025-01-21YIXING INST OF FOOD & BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411569505.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Due to its strong water absorption, sodium hyaluronate is added directly to the hydrophilic colloid system, which will cause the internal network structure of the gel to become loose, the gel performance will weaken, and the Q-supplemental and refreshing characteristics of the cold crystal ball.

Method used

By loading hyaluronic acid and mixed collagen, the load is 0.1 to 1 %, and the physical analyzer is used for hardness, elasticity, rupture strength and toughness testing to ensure the hardness of the cold sky crystal ball ≥250g, elasticity ≥45 %, and the rupture strength ≥55g, toughness ≥2.5mm.

Benefits of technology

It improves the taste of Hantian Crystal Balls, increases the smoothness, and increases the hyaluronic acid content in Hantian Crystal Balls, giving Hantian Crystal Balls a certain nutritional value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326132A_ABST
    Figure CN119326132A_ABST
Patent Text Reader

Abstract

Sodium hyaluronate and konjac glucomannan treated with different deacetylation degrees are mixed, kappa-carrageenan, sodium alginate and high-acyl gellan gum are added to prepare the hyaluronic-acid-containing chilblain spheres, the hardness of the hyaluronic-acid-containing chilblain spheres is larger than or equal to 250 g, the elasticity of the hyaluronic-acid-containing chilblain spheres is larger than or equal to 45%, the breaking strength of the hyaluronic-acid-containing chilblain spheres is larger than or equal to 55 g, and the toughness of the hyaluronic-acid-containing chilblain spheres is larger than or equal to 2.5 mm. The prepared chilblain balls are tough, smooth and optimal in taste, the content of hyaluronic acid in the chilblain balls is increased, and the chilblain balls are endowed with certain nutritional value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrophilic colloid gel, and in particular relates to a hyaluronic acid-containing agar crystal ball and a preparation method thereof. Background Art

[0002] The term Kanten originated in Japan, because in the winter of the Edo period, someone found that dried seaweed placed outdoors had the characteristic of condensation, so it was named "Kanten". In traditional Chinese medicine, it is also called "agar" or "agar gel" (English name: Agar). With the development of the beverage industry, more and more consumers tend to drink fruit tea and fruit tea. Kanten, as a new type of beverage condiment, is becoming more and more popular because of its chewy and refreshing taste and rich taste. Compared with other condiments, Kanten also has excellent characteristics such as low calories and no effect on the appearance of juice. It is currently favored by more and more restaurants or milk tea shops.

[0003] Sodium hyaluronate (hyaluronic acid) is widely present in the body, and has multiple physiological functions such as anti-aging, moisturizing, lubrication, wound healing, tissue repair and regeneration, antibacterial and anti-inflammatory. In recent years, sodium hyaluronate (hyaluronic acid) can be added to foods such as dairy products, beverages, candies, etc. as a new food raw material, to supplement the deficiency of endogenous hyaluronic acid. Exogenous hyaluronic acid is degraded, absorbed and synthesized again in the body after oral administration, and the precursor of hyaluronic acid synthesis in the body is increased, and the hyaluronic acid content in the body is improved and centrally positioned in the skin tissue, and then the water retention capacity of the skin is enhanced, and the skin stratum corneum is softened, and the elasticity of the skin is improved, wrinkles are reduced, and the activation of systemic cells is achieved to play an overall beauty and health care effect, so the food containing hyaluronic acid is increasingly taken seriously. If hyaluronic acid is added in agar crystal ball, the use value of agar crystal ball can be increased, so that it has certain health care functions.

[0004] However, since sodium hyaluronate (hyaluronic acid) is highly water-absorbent and has a large number of hydroxyl and carboxyl groups, adding it directly to the hydrophilic colloid system will compete with the hydrophilic colloid for water and interact with it, causing the internal network structure of the gel to become loose, the gel performance to be weakened, and the agar-agar crystal ball to lose its chewy and refreshing characteristics. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a kind of agar crystal ball containing hyaluronic acid.

[0008] In order to solve the above technical problems, the present invention provides the following technical solution: the agar crystal ball containing hyaluronic acid meets the following conditions:

[0009] (i) Hyaluronic acid is loaded by mixed colloids at a loading of 0.1 to 1%;

[0010] (ii) using a physical property analyzer in TDT-Hold mode with a P / 36R flat-bottom test probe, with a speed of 3.0 mm / s before the test, 1.5 mm / s during the test, and 3.0 mm / s after the test. The first compression is 40% and maintained for 30 seconds. The second compression is 60%. When the trigger force is 5.0 g, the hardness of the agarwood crystal ball is ≥ 250 g and the elasticity is ≥ 45%;

[0011] (iii) Using the Compression mode of the physical property analyzer with a P / 2 test probe, the speed before the test is 1.0 mm / s, the speed during the test is 1.5 mm / s, and the speed after the test is 3.0 mm / s. The compression degree is 70%, and the trigger force is 5.0 g. When measured, the fracture strength of the agarwood crystal ball is ≥55 g, and the toughness is ≥2.5 mm.

[0012] It should be noted that when the hardness of the agar crystal ball is ≥250g, the elasticity is ≥45%, the breaking strength is ≥55g, and the toughness is ≥2.5mm, the agar crystal ball is tough and smooth, and has the best taste;

[0013] When the hardness, elasticity, breaking strength and toughness of the agar-agar crystal ball are lower than the above values, the texture is soft and the taste is poor.

[0014] Another object of the present invention is to provide a method for preparing agar crystal balls containing hyaluronic acid.

[0015] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0016] After the hyaluronic acid solution is heated, NaHCO3 and konjac flour are added thereto to deacetylate the konjac to obtain a deacetylated colloidal solution;

[0017] Furthermore, the deacetylation treatment of konjac refers to treating konjac in an alkaline or weak alkaline solution for a period of time to modify the structure of konjac to a certain extent, thereby enhancing its gel properties. In the agar crystal ball system of the present invention, it is only applicable to the weak base treatment of NaHCO3. Strong base treatment will cause the system to experience instability such as phase separation.

[0018] In the deacetylation treatment of konjac, a single treatment time is 5 min to 20 min, for example, 5 min, 10 min, 15 min, 20 min or any range therebetween.

[0019] Furthermore, the mixing of various colloids can be carried out by using stirring equipment or methods commonly used in the art, such as using a chopper, a stirring paddle, etc. to make them swell evenly without agglomeration. The present invention does not impose any specific restrictions on the above steps, as long as a uniformly swollen colloidal solution can be obtained.

[0020] Add κ-carrageenan, sodium alginate, high acyl gellan gum and KCl to the deacetylated colloidal solution and stir to swell the solution to obtain a mixed colloid;

[0021] Furthermore, the mixing of various colloids can be carried out by using stirring equipment or methods commonly used in the art, such as using a chopper, a stirring paddle, etc. to make them swell evenly without agglomeration. The present invention does not impose any specific restrictions on the above steps, as long as a uniformly swollen colloidal solution can be obtained.

[0022] The mixed colloid is subjected to vacuum degassing treatment and then heated to obtain a mixed colloid solution;

[0023] Furthermore, in order to prevent the small bubbles in the colloid from affecting the texture and appearance of the crystal sphere, the bubble removal treatment can be carried out by using a commonly used bubble removal device or method in the art, such as a vacuum stirring reactor, a vacuum drying oven, etc. to remove the bubbles. The present invention does not impose any specific restrictions on the above steps, as long as a bubble-free colloid solution can be obtained.

[0024] In order to make the colloidal powder further fully swell and uniformly heat-treat, commonly used heating equipment or methods in the art can be used, such as stirring and heating in a water bath, stirring and heating directly in an electric furnace, etc. The present invention does not make any specific restrictions on the above steps, and a fully swelled and uniform colloidal solution is sufficient.

[0025] The mixed colloidal solution is dripped into the molding liquid by extrusion, and the molding liquid is treated in an ice bath to obtain a molded crystal ball.

[0026] Furthermore, in order to make the crystal ball present a better shape, the method of manual extrusion or ball dropping machine can be selected to drop the glue into the molding liquid. As for the specific method of dropping the ball, technicians in this field can freely choose from the existing technology, and this application does not make any specific restrictions.

[0027] The calcium lactate and KCl in the forming liquid of the present invention mainly interact with the sodium alginate, high acyl gellan gum and kappa-carrageenan in the gel solution to synergistically enhance the texture and structure of the crystal spherical gel.

[0028] The formed crystal balls are immersed in a protective solution and sterilized to obtain the agar crystal balls containing hyaluronic acid of this embodiment.

[0029] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the mixed colloid comprises, in terms of weight percentage,

[0030] 0.1% to 1.0% hyaluronic acid, 0.08% to 0.64% NaHCO3, 1.2% to 1.35% konjac flour, 0.9% to 1.05% κ-carrageenan, 0.3% to 0.45% sodium alginate, 0.3% to 0.45% high acyl gellan gum, and 0.2% to 0.5% KCl.

[0031] Hyaluronic acid (HA), also known as hyaluronic acid, is a disaccharide unit glycosaminoglycan composed of D-glucuronic acid and N-acetylglucosamine. It generally refers to hyaluronate, including sodium hyaluronate, potassium hyaluronate, calcium hyaluronate, zinc hyaluronate, and magnesium hyaluronate.

[0032] The hyaluronic acid used in the present invention is sodium hyaluronate unless otherwise specified.

[0033] In some embodiments of the present application, the molecular weight of the hyaluronic acid used is 8 to 4 million. For example, the molecular weight of the hyaluronic acid used can be 80,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1 million, 1.1 million, 1.2 million, 1.3 million, 1.4 million, 1.5 million, 1.6 million, 1.7 million, 1.8 million, 1.9 million, 2 million, 2.1 million, 2.2 million, 2.3 million, 2.4 million, 2.5 million, 2.6 million, 2.7 million, 2.8 million, 2.9 million, 3 million, 3.3 million, 3.5 million, 3.8 million, 4 million or any range therebetween.

[0034] In some embodiments of the present application, in the agar-agar crystal balls containing hyaluronic acid, the hyaluronic acid accounts for 0.1% to 1.0% of the total mass, calculated as a percentage by weight of the mixed colloid. For example, the hyaluronic acid accounts for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% of the total mass or any range therebetween.

[0035] In some embodiments of the present application, in the agar-agar crystal ball containing hyaluronic acid, NaHCO3 accounts for 0.08% to 0.64% of the total mass, calculated as a percentage by weight of the mixed colloid, for example, NaHCO3 accounts for 0.08%, 0.12%, 0.16%, 0.20%, 0.24%, 0.28%, 0.32%, 0.36%, 0.40%, 0.44%, 0.48%, 0.52%, 0.56%, 0.60%, 0.64% of the total mass or any range therebetween.

[0036] Konjac flour is a powder made by removing impurities such as starch, alkaloids, and tannins from konjac flour and then dehydrating and drying it. Konjac glucomannan is the main component of konjac, and the repeating sugar units are mannose and glucose. The two are connected by a β-1,4 glycosidic bond. As a non-ionic high molecular weight polysaccharide, KGM has the properties of water retention, emulsification, and thickening.

[0037] In some embodiments of the present application, in the agar-agar balls containing hyaluronic acid, konjac flour accounts for 1.2% to 1.35% of the total mass, calculated as a percentage by weight of the mixed colloid, for example, konjac flour accounts for 1.2%, 1.25%, 1.3%, 1.35% of the total mass or any range therebetween.

[0038] Carrageenan, also known as carrageenan, is a type of non-uniform water-soluble linear polysaccharide extracted from the cell wall of red algae. It is a high molecular polymer formed by the combination of 1,3-β-D-galactopyranose and 1,4-α-D-galactopyranose as the basic skeleton. There are three main types of carrageenan: κ, I, and λ. Among them, κ-carrageenan can be widely used in the food industry as a gelling agent, water retaining agent, antifreeze agent, etc.

[0039] In some embodiments of the present application, in the agar-agar balls containing hyaluronic acid, kappa-carrageenan accounts for 0.9% to 1.05% of the total mass, measured as a weight percentage of the mixed colloid, for example, kappa-carrageenan accounts for 0.9%, 0.95%, 1.0%, 1.05% of the total mass or any range therebetween.

[0040] Sodium alginate is a byproduct of extracting iodine and mannitol from brown algae such as kelp or sargassum. Its molecule is composed of α-l-guluronic acid (G unit) and β-d-mannuronic acid (M unit) connected by 1,4-glycosidic bonds, in which the G block can be connected with Ca 2+ Chelation forms a thermally irreversible gel, and the "egg-box gel network" formed by SA / Ca2+ has excellent mechanical properties.

[0041] In some embodiments of the present application, in the agar-agar crystal ball containing hyaluronic acid, sodium alginate accounts for 0.3% to 0.45% of the total mass by weight, for example, sodium alginate accounts for 0.3%, 0.35%, 0.4%, 0.45% of the total mass or any range therebetween.

[0042] Gellan gum is a macromolecular polysaccharide produced by fermentation of Sphingomonas oligomobilis isolated from Elodea plant tissue under aerobic conditions. Gellan gum is an anionic linear macromolecular polysaccharide with a relative molecular mass of 300-600kDa, and its basic structural composition includes repeated tetrasaccharide units. According to the acyl content, gellan gum can be divided into two categories: high acyl gellan gum and low acyl gellan gum. Gellan gum reacts with calcium ions to form a thermally stable (thermally irreversible) gel system, and high acyl gellan gum forms a viscoelastic and soft gel. Therefore, it is widely used in foods such as puddings, jellies, beverages, dairy products, jam products, bread fillings, surface smootheners, candies, etc.

[0043] In some embodiments of the present application, in the agar-agar crystal balls containing hyaluronic acid, high acyl gellan gum accounts for 0.3% to 0.45% of the total mass by weight, for example, high acyl gellan gum accounts for 0.3%, 0.35%, 0.4%, 0.45% of the total mass or any range therebetween.

[0044] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the hyaluronic acid solution is heated at a temperature of 85° C. to 100° C. and the heating time is 8 to 15 minutes.

[0045] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the initial pH of the hyaluronic acid solution is 4 to 4.5, and the pH after heating treatment is 6.5 to 7.5.

[0046] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the heating temperature of the mixed colloid after vacuum degassing treatment is 75°C to 95°C, and the heating time is 3 to 5 minutes.

[0047] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the molding liquid comprises the following: the mass concentration of calcium lactate is 3% to 5%, the mass concentration of KCl is 2% to 4%, and the mass concentration of sodium carboxymethyl cellulose is 0.5% to 1%.

[0048] Furthermore, in some embodiments of the present application, in the molding liquid, calcium lactate accounts for 3% to 5% of the total mass of the molding liquid by weight percentage, for example, calcium lactate accounts for 3%, 3.5%, 4%, 4.5%, 5% or any range therebetween of the total mass of the molding liquid.

[0049] KCl accounts for 2% to 4% of the total mass of the molding liquid. For example, KCl accounts for 2%, 2.5%, 3%, 3.5%, 4% or any range therebetween of the total mass of the molding liquid.

[0050] As a preferred solution of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the protective solution contains erythritol at a mass concentration of 25% to 35% and edible flavor at a mass concentration of 0.1% to 0.5%.

[0051] Furthermore, in some embodiments of the present application, in the protective solution, erythritol accounts for 25% to 35% of the total mass of the protective solution by weight percentage, for example, erythritol accounts for 25%, 30%, 35% or any range therebetween of the total mass of the molding solution.

[0052] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the mixed colloid solution is kept in the molding liquid for 3 to 7 minutes.

[0053] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the ice bath treatment time is 1 to 1.5 hours.

[0054] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the pH value of the protective solution is 3-4.

[0055] Furthermore, in some embodiments of the present application, the pH of the protective solution is pH 2.5, pH 3, pH 3.5, pH 4 or any range therebetween.

[0056] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar balls of the present invention, the immersion time of the formed crystal balls in the protective solution is 10 to 30 minutes, wherein the mass ratio of the formed crystal balls to the protective solution is 5:5 to 8:2.

[0057] As a preferred embodiment of the method for preparing the hyaluronic acid-containing agar crystal balls of the present invention, the sterilization treatment is performed at a temperature of 85° C. to 95° C. for 25 to 35 minutes.

[0058] In some embodiments of the present application, the agar crystal ball further includes adding additives acceptable in the food field to the protective liquid, including preservatives and flavors acceptable in the food field, the preservatives including benzoic acid and salts, potassium sorbate, sodium dehydroacetate, propyl paraben, calcium propionate, sodium diacetate, etc.; the flavors include natural flavors, equivalent natural flavors, artificial synthetic flavors, flavors prepared by microbial methods, etc. The amount of additives added can be freely selected by those skilled in the art according to actual needs.

[0059] In some embodiments of the present application, in the colloid swelling step, the aqueous solution may be an aqueous solution to which additives acceptable in the food field are added, and the additives include preservatives and flavors acceptable in the food field, and the preservatives include benzoic acid and salts, potassium sorbate, sodium dehydroacetate, propyl paraben, calcium propionate, sodium diacetate, etc.; the acidity regulator includes citric acid, malic acid, tartaric acid, lactic acid, etc.; the flavor includes natural flavors, equivalent natural flavors, artificial synthetic flavors, flavors prepared by microbial methods, etc. For the amount of additives added, those skilled in the art can freely choose according to actual needs.

[0060] Beneficial effects of the present invention:

[0061] The invention prepares agar balls containing hyaluronic acid by mixing hyaluronic acid with konjac gum treated with different degrees of deacetylation and then adding kappa-carrageenan, sodium alginate and high acyl gellan gum, which can improve the taste of the agar balls, enhance the smoothness, increase the loading amount of hyaluronic acid in the agar balls, and endow the agar balls with certain nutritional value. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0063] Figure 1 This is a physical picture of the agarwood crystal ball prepared in Example 1 of the present invention;

[0064] Figure 2 This is a physical picture of the glue solution prepared in Comparative Example 2 of the present invention;

[0065] Figure 3 This is a physical picture of the agarwood crystal ball prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0066] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0067] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0068] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0069] The present application provides a general and / or specific description of the materials and experimental methods used in the experiments. In the following embodiments, the reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially, among which sodium hyaluronate was purchased from Bloomage Biotech Co., Ltd.

[0070] The performance testing method of the product of the present invention is:

[0071] The hardness was measured using the physical property analyzer TDT-Hold mode (P / 36R probe, speed before test: 3.0 mm / s, speed during test: 1.5 mm / s, speed after test: 3.0 mm / s, the first compression degree was 40%, and it was maintained for 30 seconds; the second compression degree was 60%, and the trigger force was 5.0 g);

[0072] The elasticity was measured using the physical property analyzer TDT-Hold mode (P / 36R probe, speed before test: 3.0 mm / s, speed during test: 1.5 mm / s, speed after test: 3.0 mm / s, the first compression degree was 40%, and it was maintained for 30 seconds; the second compression degree was 60%, and the trigger force was 5.0 g);

[0073] Use the Compression mode of the physical property analyzer (probe selection P / 2, speed before test: 1.0mm / s, speed during test: 1.5mm / s, speed after test: 3.0mm / s, compression degree of 70%, trigger force 5.0g) to measure the burst strength;

[0074] The toughness was measured using the Compression mode of the physical property analyzer (probe selection P / 2, speed before test: 1.0 mm / s, speed during test: 1.5 mm / s, speed after test: 3.0 mm / s, compression degree of 70%, trigger force 5.0 g).

[0075] The sensory preliminary test results of purchasing commercially available agar crystal balls and preparing agar crystal balls of different textures are shown in Table 1. (The meaning of the preference score: 1 - extremely dislike; 2 - very dislike; 3 - moderate dislike; 4 - slightly dislike; 5 - neither like nor dislike; 6 - slightly like; 7 - moderate like; 8 - very like; 9 - extremely like)

[0076] Table 1

[0077] Likeability Hardness / g elasticity / % Bursting strength / g Toughness / mm 9 386.34±24.87 54.98±0.45 74.29±3.09 2.91±0.93 8 355.16±26.43 50.26±0.12 68.21±2.47 2.85±0.22 7 321.72±29.84 49.23±0.29 67.47±2.09 2.69±0.25 7 304.34±45.27 49.61±0.88 67.22±3.13 2.72±0.13 5 268.31±34.77 46.14±2.39 57.10±2.48 2.62±0.62 5 255.98±17.38 45.87±3.09 55.97±1.99 2.55±0.41 4 221.25±21.47 42.81±1.12 36.61±5.61 2.42±0.30 4 220.31±13.67 40.14±2.02 40.23±1.19 2.23±0.21 3 189.55±10.25 42.34±0.98 26.98±0.99 2.06±0.91 3 165.42±2.41 41.02±0.24 30.66±1.87 1.67±0.06

[0078] The present invention has concluded through preliminary experiments that when the hardness of the agar crystal ball is ≥250g, the elasticity is ≥45%, the rupture strength is ≥55g, and the toughness is ≥2.5mm, the agar crystal ball is tough and smooth, and has the best taste; when the hardness, elasticity, rupture strength and toughness of the agar crystal ball are lower than the above values, the texture is soft and the taste is poor.

[0079] Example 1

[0080] This embodiment provides a method for preparing agar crystal balls containing hyaluronic acid, specifically:

[0081] 1) 4 g of sodium hyaluronate (molecular weight 400,000) was dissolved in 382.56 g of water, and the pH was adjusted to 4 with citric acid to obtain a sodium hyaluronate solution;

[0082] After the sodium hyaluronate solution is heated, the pH is adjusted to 7, and 0.64 g of NaHCO3 and 5.4 g of konjac flour are added thereto for deacetylation. The treatment time is 10 min to obtain a deacetylated colloidal solution;

[0083] Add 4.2 g of κ-carrageenan, 1.2 g of sodium alginate, 1.2 g of high acyl gellan gum, and 0.8 g of KCl to the deacetylated colloidal solution, stir and swell thoroughly, and obtain a mixed colloid;

[0084] The mixed colloid is subjected to vacuum degassing treatment and then heated at 95° C. for 4 min to obtain a mixed colloid solution, wherein the mass concentration of sodium hyaluronate is 1%, the mass concentration of NaHCO3 is 0.16%, the mass concentration of konjac flour is 1.35%, the mass concentration of κ-carrageenan is 1.05%, the mass concentration of sodium alginate is 0.3%, the mass concentration of high acyl gellan gum is 0.3%, and the mass concentration of KCl is 0.2%;

[0085] 2) 10g of calcium lactate, 4g of potassium chloride, and 1g of sodium carboxymethyl cellulose are placed in a container, and 185g of water is added to completely dissolve them to obtain a molding liquid with a calcium lactate mass concentration of 5%, a potassium chloride mass concentration of 2%, and a sodium carboxymethyl cellulose mass concentration of 0.5%;

[0086] The mixed colloidal solution was dripped into the molding liquid by extrusion and kept for 5 minutes. After molding, the mixture was treated in an ice bath for 1 hour to obtain a molded crystal sphere.

[0087] 3) 28 g of erythritol and 0.5 g of natural flavor were dissolved in 70.5 g of water, stirred evenly, and the pH of the solution was adjusted to 4 to obtain a protective solution with an erythritol mass concentration of 28% and a natural flavor mass concentration of 0.5%;

[0088] The formed crystal balls are immersed in a protective solution and sterilized at 95° C. for 30 minutes to obtain the agar crystal balls containing hyaluronic acid in this embodiment.

[0089] Figure 1 This is a physical picture of the agar-agar crystal ball prepared in Example 1. It can be seen that it has good texture characteristics.

[0090] Example 2

[0091] The difference between this embodiment and embodiment 1 is that the concentration of the colloidal solute in the mixed colloidal solution is adjusted, specifically:

[0092] The amount of konjac flour, the amount of κ-carrageenan, and the amount of sodium alginate are adjusted to 4.8 g, 3.6 g, and 1.8 g, that is, the mass concentration of konjac flour in the prepared mixed colloid solution is 1.2%, the mass concentration of κ-carrageenan is 0.9%, and the mass concentration of sodium alginate is 0.5%;

[0093] The remaining steps and processes are all referred to Example 1 to obtain the agar crystal ball containing hyaluronic acid in this example.

[0094] Example 3

[0095] The difference between this embodiment and embodiment 1 is that the concentration of NaHCO3 in the mixed colloidal solution is adjusted, specifically:

[0096] The amount of NaHCO3 was adjusted to 1.28 g, that is, the mass concentration of NaHCO3 in the prepared mixed colloidal solution was 0.32%;

[0097] The remaining steps and processes are all referred to Example 1 to obtain the agar crystal ball containing hyaluronic acid in this example.

[0098] Example 4

[0099] The difference between this embodiment and embodiment 1 is that the concentration of sodium hyaluronate in the mixed colloidal solution is adjusted, specifically:

[0100] The amount of sodium hyaluronate in step 1) is adjusted to 2 g, that is, the mass concentration of sodium hyaluronate in the prepared mixed colloidal solution is 0.5%;

[0101] The remaining steps and processes are all referred to Example 1 to obtain the agar crystal ball containing hyaluronic acid in this example.

[0102] Example 5

[0103] The difference between this embodiment and embodiment 1 is that the pH of the protective solution in step 3) is adjusted to 3, and the remaining steps and processes are all referred to embodiment 1 to obtain the agar crystal balls containing hyaluronic acid in this embodiment.

[0104] Example 6

[0105] The difference between this embodiment and embodiment 1 is that the molecular weight of sodium hyaluronate, the concentration of the colloidal solute in the mixed colloidal solution and the pH of the protective solution are adjusted. Specifically:

[0106] In step 1), the molecular weight of sodium hyaluronate is adjusted to 1.8 million, the amount of konjac flour is 4.8 g, the amount of κ-carrageenan is 3.6 g, the amount of sodium alginate is 1.8 g, and the amount of high acyl gellan gum is 1.8 g, that is, the mass concentration of konjac flour in the prepared mixed colloidal solution is 1.2%, the mass concentration of κ-carrageenan is 0.9%, the mass concentration of sodium alginate is 0.5%, and the mass concentration of high acyl gellan gum is 0.5%;

[0107] The pH of the protective solution in step 3) is adjusted to 3, and the remaining steps are carried out according to Example 1 to obtain the agar crystal ball containing hyaluronic acid of this example.

[0108] Example 7

[0109] The difference between this embodiment and embodiment 1 is that the concentration of NaHCO3 in the mixed colloidal solution and the pH of the protective solution are adjusted to 3. Specifically:

[0110] The amount of NaHCO3 is adjusted to 1.28 g, that is, the mass concentration of NaHCO3 in the prepared mixed colloidal solution is 0.32%, the pH of the protective solution in step 3) is 3, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal ball containing hyaluronic acid in this example.

[0111] Example 8

[0112] The difference between this embodiment and embodiment 1 is that the concentration of sodium hyaluronate in the mixed colloidal solution and the pH of the protective solution are adjusted to 3. Specifically:

[0113] The amount of sodium hyaluronate in step 1) is adjusted to 2 g, that is, the mass concentration of sodium hyaluronate in the prepared mixed colloidal solution is 0.5%, the pH of the protective solution in step 3) is 3, and the remaining steps and processes are all referred to Example 1 to obtain the agar-agar crystal ball containing hyaluronic acid in this example.

[0114] Comparative Example 1

[0115] This comparative example is different from Example 1 in that the konjac flour is not subjected to deacetylation treatment, specifically:

[0116] 1) 5.4 g konjac flour, 4.2 g kappa-carrageenan, 1.2 g sodium alginate, 1.2 g high acyl gellan gum, 0.8 g KCl, and 4 g sodium hyaluronate (molecular weight 400,000) were dissolved in 383.2 g water, and the pH was adjusted to 4 with citric acid to obtain a mixed colloid;

[0117] The mixed colloid was subjected to vacuum degassing treatment and then heated at 95°C for 4 minutes to obtain a mixed colloid solution;

[0118] Among them, the mass concentration of sodium hyaluronate is 1%, the mass concentration of konjac flour is 1.35%, the mass concentration of κ-carrageenan is 1.05%, the mass concentration of sodium alginate is 0.3%, the mass concentration of high acyl gellan gum is 0.3%, and the mass concentration of KCl is 0.2%;

[0119] 2) 10g calcium lactate, 4g potassium chloride, and 1g sodium carboxymethyl cellulose are placed in a container, and 185g water is added to completely dissolve them to obtain a molding liquid;

[0120] The mixed colloidal solution was dripped into the molding liquid by extrusion and kept for 5 minutes. After molding, the mixture was treated in an ice bath for 1 hour to obtain a molded crystal sphere.

[0121] 3) 28 g of erythritol and 0.5 g of natural flavor were dissolved in 70.5 g of water, stirred evenly, and the pH of the solution was adjusted to 4 to obtain a protective solution;

[0122] The formed crystal balls were immersed in a protective solution and sterilized at 95° C. for 30 min to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0123] Comparative Example 2

[0124] This comparative example is different from Example 1 in that konjac flour is not deacetylated and the concentration of total glue is increased, specifically:

[0125] 1) 8 g konjac flour, 6 g κ-carrageenan, 3 g sodium alginate, 3 g high acyl gellan gum, 0.8 g KCl, and 4 g sodium hyaluronate (molecular weight 400,000) were dissolved in 383.2 g water, and the pH was adjusted to 4 with citric acid to obtain a mixed colloid;

[0126] The mixed colloid was subjected to vacuum degassing treatment and then heated at 95°C for 4 minutes to obtain a mixed colloid solution;

[0127] Among them, the mass concentration of sodium hyaluronate is 1%, the mass concentration of konjac flour is 2%, the mass concentration of κ-carrageenan is 1.5%, the mass concentration of sodium alginate is 0.75%, the mass concentration of high acyl gellan gum is 0.75%, and the mass concentration of KCl is 0.2%;

[0128] Figure 2 This is a physical picture of the colloidal solution. It can be seen that the colloidal solution is very viscous.

[0129] 2) 10g of calcium lactate, 4g of potassium chloride, and 1g of sodium carboxymethyl cellulose are placed in a container, and 185g of water is added to completely dissolve them to obtain a molding liquid with a calcium lactate mass concentration of 5%, a potassium chloride mass concentration of 2%, and a sodium carboxymethyl cellulose mass concentration of 0.5%;

[0130] The mixed colloidal solution was dripped into the molding liquid by extrusion and kept for 5 minutes. After molding, the mixture was treated in an ice bath for 1 hour to obtain a molded crystal sphere.

[0131] 3) 28 g of erythritol and 0.5 g of natural flavor are dissolved in 70.5 g of water, stirred evenly, and the pH of the solution is adjusted to 4 to obtain a protective solution with a mass concentration of erythritol of 28%, a mass concentration of sodium hyaluronate of 1%, and a mass concentration of natural flavor of 0.5%;

[0132] The formed crystal balls were immersed in a protective solution and sterilized at 95° C. for 30 min to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0133] Comparative Example 3

[0134] The difference between this comparative example and Example 1 is that the NaHCO3 used for deacetylation of konjac flour in step 1) is adjusted to Na2CO3, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example. Figure 3 This is a physical picture of the cold-weather crystal ball prepared in this comparative example.

[0135] Comparative Example 4

[0136] The difference between this comparative example and Example 1 is that the pH of the protective solution in step 3) is adjusted to 2.5, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0137] Comparative Example 5

[0138] The difference between this comparative example and Example 1 is that no konjac powder is added, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0139] Comparative Example 6

[0140] The difference between this comparative example and Example 1 is that κ-carrageenan is not added, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0141] Comparative Example 7

[0142] The difference between this comparative example and Example 1 is that high acyl gellan gum is not added, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0143] Comparative Example 8

[0144] The difference between this comparative example and Example 1 is that sodium alginate is not added, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0145] Comparative Example 9

[0146] The difference between this comparative example and Example 1 is that the NaHCO3 content in the deacetylation treatment of konjac flour in step 1) is adjusted to 0.8%, and the remaining steps and processes are all referred to Example 1 to obtain the agar crystal balls containing hyaluronic acid in this comparative example.

[0147] The texture analysis of the hyaluronic acid agar-agar crystal spheres was performed using a physical property analyzer, and the effects of hardness, elasticity, rupture strength and toughness of the agar-agar crystal spheres prepared in each embodiment and control example were measured respectively. The measured data are recorded in Table 2.

[0148] Table 2

[0149]

[0150]

[0151] It can be seen from Table 2 that the hardness, elasticity and rupture strength of the agar-agar crystal balls prepared in the embodiments of the present invention are all within an acceptable range, indicating that the agar-agar crystal balls prepared in the embodiments of the present invention have good hardness, elasticity, rupture strength and toughness.

[0152] The konjac flour in comparative example 1 was not deacetylated, and hyaluronic acid directly affected the overall gel network structure. The agar balls had a soft texture and low elasticity. If 1% hyaluronic acid was directly added without deacetylation, the gel strength was very weak and a complete gel structure could not be formed.

[0153] In Comparative Example 2, the konjac flour was not deacetylated, and the concentration of the total gel was increased, so the gel was very viscous. However, the hyaluronic acid still affected the overall gel network structure, and the mouthfeel of the agar-agar crystal ball was still soft and less elastic.

[0154] The konjac flour of Comparative Example 3 was deacetylated using Na2CO3, resulting in phase separation. The agar balls had a soft texture, low elasticity, and a layered structure.

[0155] The pH of the protective liquid of the agar-agar crystal balls in Comparative Example 4 was 2.5. The overly acidic environment caused the agar-agar crystal balls to have a soft texture, low elasticity, and reduced rupture strength.

[0156] In Comparative Example 5, no konjac flour was added to the agar crystal balls, and the agar crystal balls had a soft texture and weakened elasticity; in Comparative Example 6, no κ-carrageenan was added to the agar crystal balls, and the agar crystal balls had a soft texture and reduced breaking strength; in Comparative Example 7, no high acyl gellan gum was added to the agar crystal balls, and the agar crystal balls had a soft texture and weakened elasticity; in Comparative Example 8, no sodium alginate was added to the agar crystal balls, and the agar crystal balls could not be formed.

[0157] The konjac flour of Comparative Example 9 was deacetylated using excess NaHCO3, resulting in phase separation, reduced elasticity in the mouthfeel of the agar-agar crystal balls, and a layered structure.

[0158] In summary, the present invention prepares agar balls containing hyaluronic acid by mixing sodium hyaluronate with konjac gum treated with different degrees of deacetylation and then adding κ-carrageenan, sodium alginate and high acyl gellan gum, which can improve the taste of the crystal balls, enhance the smoothness, increase the content of hyaluronic acid in the agar balls, and give the agar balls certain nutritional value.

[0159] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A crystal ball containing hyaluronic acid, characterized in that: The following conditions are met, (i) Hyaluronic acid is loaded by mixed colloids at a loading of 0.1 to 1%; (ii) using a physical property analyzer in TDT-Hold mode with a P / 36R flat-bottom test probe, with a speed of 3.0 mm / s before the test, 1.5 mm / s during the test, and 3.0 mm / s after the test. The first compression is 40% and maintained for 30 seconds. The second compression is 60%. When the trigger force is 5.0 g, the hardness of the agarwood crystal ball is ≥ 250 g and the elasticity is ≥ 45%; (iii) Using the Compression mode of the physical property analyzer with a P / 2 test probe, the speed before the test is 1.0 mm / s, the speed during the test is 1.5 mm / s, and the speed after the test is 3.0 mm / s. The compression degree is 70%, and the trigger force is 5.0 g. When measured, the fracture strength of the agarwood crystal ball is ≥55 g, and the toughness is ≥2.5 mm.

2. A method for preparing agar crystal balls containing hyaluronic acid, characterized in that: include, After the hyaluronic acid solution is heated, NaHCO3 and konjac flour are added thereto to deacetylate the konjac to obtain a deacetylated colloidal solution; Adding hydrophilic colloid and salt ions to the deacetylated colloidal solution and fully stirring and swelling to obtain a mixed colloid, and heating the mixed colloid after vacuum degassing to obtain a mixed colloid solution; Wherein, the hydrophilic colloid is composed of κ-carrageenan, sodium alginate, and high acyl gellan gum, and the salt ion is KCl. In terms of the mass percentage of the mixed colloid solution, it includes: 0.1% to 1.0% hyaluronic acid, 0.08% to 0.64% NaHCO3, 1.2% to 1.35% konjac flour, 0.9% to 1.05% kappa-carrageenan, 0.3% to 0.45% sodium alginate, 0.3% to 0.45% high acyl gellan gum, 0.2% to 0.5% KCl, and the balance is water; The mixed colloidal solution is squeezed and dripped into the molding liquid for 3 to 7 minutes, and then treated in an ice bath for 1 to 1.5 hours after molding to obtain a molded crystal ball; The formed crystal balls are immersed in a protective solution and sterilized to obtain agar crystal balls containing hyaluronic acid.

3. The method for preparing the agar crystal ball containing hyaluronic acid as claimed in claim 2, characterized in that: The heating treatment time of the hyaluronic acid solution is 85°C to 100°C, and the heating time is 8 to 15 minutes; the pH of the hyaluronic acid solution before heating is 4 to 4.5, and the pH of the hyaluronic acid solution after heating is adjusted to 6.5 to 7.

5.

4. The method for preparing the agar crystal ball containing hyaluronic acid as claimed in claim 2, characterized in that: The treatment time of the konjac deacetylation treatment is 5 min to 20 min.

5. The method for preparing agar crystal balls containing hyaluronic acid as claimed in claim 2, characterized in that: The mixed colloid is subjected to vacuum degassing treatment and then heated, wherein the heating temperature is 75° C. to 95° C. and the heating time is 3 to 5 minutes.

6. The method for preparing agar crystal balls containing hyaluronic acid as claimed in claim 2, characterized in that: The molding liquid comprises calcium lactate, KCl and sodium carboxymethyl cellulose, wherein the mass concentration of calcium lactate is 3% to 5%, the mass concentration of KCl is 2% to 4%, and the mass concentration of sodium carboxymethyl cellulose is 0.5% to 1%.

7. The method for preparing agar crystal balls containing hyaluronic acid as claimed in claim 2, characterized in that: The protective solution contains erythritol and edible flavoring, wherein the mass concentration of erythritol is 25% to 35%, and the mass concentration of edible flavoring is 0.1% to 0.5%.

8. The method for preparing agar-agar crystal balls containing hyaluronic acid according to any one of claims 2 or 7, characterized in that: The shaped crystal ball is immersed in the protection liquid for 10 to 30 minutes, wherein the mass ratio of the shaped crystal ball to the protection liquid is 5:5 to 8:

2.

9. The method for preparing agar crystal balls containing hyaluronic acid as claimed in claim 7, characterized in that: The pH of the protective solution is 3-4.

10. The method for preparing agar crystal balls containing hyaluronic acid as claimed in claim 2, characterized in that: The sterilization treatment is carried out at a temperature of 85°C to 95°C and for a time of 25 to 35 minutes.